Effect of stocking rate on the pasture and sheep production in winter and spring lambing systems - Ozcan G.; Ates S.; Kirbas M.; Cicek H.; Isik S. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
A two-year study investigated the effect of stocking rate on the pasture productivity and lamb performance in winter and spring lambing systems. Pastures were grazed at low (16-20 ewes + lambs ha-1), medium (24-28 ewes + lambs ha-1) and high (32-36 ewes + lambs ha-1) stocking rates in spring 2012 and 2013. Annual pasture dry matter (DM) productions ranged from 8.9 to 10.2 t ha−1 but were not affected by the stocking rate. The average daily live weight gains of the winter born lambs were 73 and 10 g head-1d-1 for low and medium stocking rates, respectively, while the lambs at the high stocking rate lost 10 g head-1d-1 in spring 2012. The spring born lambs grew at 245, 189, 133 g head-1d-1 for low, medium, and high stocking rates, respectively, in spring 2013. High stocking rates did not have any negative effect on the pasture production but they resulted in poor sheep performances.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)